On the adsorbate restructuring induced hysteresis of simple gas adsorption in slit micropores - Diao, R.; Fan, Chunyan; Do, D.; Nicholson, D. (Elsevier BV, 2016)
Simulations of adsorption isotherms for simple gases in homogeneous slit pores with two open ends often show hysteresis, between condensation and evaporation branches. The hysteresis may result either, from the difference in the curvature of the interface separating the adsorbed and gas phases, or from molecular restructuring when the adsorbate is densely packed. The order-disorder transition that occurs in the second case, has also been observed experimentally for adsorption on a graphite surface, and is supported by molecular simulation (Duval and Thomy, 1975; Ustinov and Do, 2012). In this paper we report a comprehensive set of GCMC simulations designed to explore the effects of pore size and temperature on the hysteresis loop induced by adsorbate restructuring. We report isotherms, isosteric heats, and microscopic analyses of the local density distribution, and the 2D and 3D radial density distributions. Local compressibilities reinforce the supposition that adsorbate restructuring is the origin of the ordering hysteresis.